Valorization of the potential use of date press cake (date syrup by-product) in food and non-food applications: a review - Alqahtani, Nashi K. (Frontiers in Sustainable Food Systems, 2024)
Date palm is the most important fruit crop in the Middle East, North Africa, and Southwest Asia. However, a large amount of waste is generated through various industries related to date processing. Date press cake (DPC) is the main by-product of the date honey or syrup industry, where it gives 17–28 g of DPC /100 g of fruit and is usually discarded as waste. Due to its higher content of nutrients and bioactive compounds, it can be valorized through inclusion in various food and nonfood applications. The potential applications of DPC as a promising ingredient and innovative substrate in different applications were discussed in this review, including chemical composition, nutritional value, functionality, current applications of DPC, limitations, and future trends.